OIDDE Learning Models on Metacognitive Skills and Cognitive Learning Outcomes of Man 1 Bulukumba Students - Sartina, Sartina; Jamilah, Jamilah; Suarga, Suarga; Damayanti, Eka (Jurusan Pendidikan Biologi - Universitas Siliwangi, 2022)
Metacognitive skills can make students aware of planning, controlling the process, evaluating, and reflecting, including assessing their weaknesses and strengths. Thus having high metacognitive skills can have high cognitive learning outcomes as well. The OIDDE learning model can improve metacognitive skills, which positively correlate with learning outcomes. This study aims to determine the effect of the OIDDE Learning Model on Metacognitive Skills and Cognitive Learning Outcomes in Biology Subjects of Students in MAN 1 Bulukumba. This study used a quasi-experimental design with a non-equivalent control group. The population comprises 86 students from MAN 1 Bulukumba class XI, 56 of whom were randomly selected using the purposive selection technique. The descriptive and inferential data analysis techniques used were the preconditioning test and the Polled variance t-test. Based on the results of the data analysis, the student's metacognitive skills average pre-test was 67.87, and the post-test was 83.5. The learning outcome of the student's pre-test was 63.33, and the post-test was 88.23. The t-test of the Polled variance showed a value of F = 7.48 of 56 and sig. (2-tailed) or p-was 0.0290.05. It may be inferred that the OIDDE learning model affects students in MAN 1 Bulukumba's metacognitive capabilities and learning outcomes in biology subjects.Â Keywords: OIDDE learning models, metacognitive skills, learning outcomesÂ